IVAN VERKHRATSKYY – A FIGHTER FOR PURITY OF THE LITERARY LANGUAGE - Lesiuk, M. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Mykola Lesiuk’s article “Ivan Verkhratskyy – a Fighter for Purity of the Literary Language” highlights the outstanding Ukrainian scholar – a natural scientist, a man of letters, a linguist, a dialectologist, who researched into Western Ukrainian folk subdialects, struggled for purity of the Ukrainian literary language on the folk basis, acutely polemicized with Moscowphiles, who imposed Old Slavonic-Russian language on inhabitants of Halychyna.